2020
DOI: 10.3390/s20216291
|View full text |Cite
|
Sign up to set email alerts
|

Modified Fixed Wall Oedometer When Considering Stress Dependence of Elastic Wave Velocities

Abstract: A modified oedometer cell for measuring the applied stresses and elastic waves at the top and bottom of the specimen is developed to evaluate the effect of the side friction on the stress dependence of the elastic wave velocities. In the modified cell, two load cells are installed at the top and bottom plates, respectively. To generate and detect the compressional and shear waves, a pair of piezo disk elements and a pair of bender elements are mounted at both the top and bottom plates. Experimental results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The fact is that the bender elements can be mounted in any geotechnical device capable of controlling stresses while measuring deformations, or vice versa, as mentioned by Ferreira [ 42 ]. Such equipment includes: odometer [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], direct shear apparatus [ 65 , 73 ], resonant-column [ 74 , 75 , 76 , 77 ], centrifuge [ 78 , 79 ], hollow cylinder [ 80 , 81 , 82 ], calibration chambers [ 83 , 84 ], true triaxial and cubical cel apparatus [ 85 , 86 ]. Some examples are presented in Section 6 .…”
Section: Modern Measuring Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact is that the bender elements can be mounted in any geotechnical device capable of controlling stresses while measuring deformations, or vice versa, as mentioned by Ferreira [ 42 ]. Such equipment includes: odometer [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], direct shear apparatus [ 65 , 73 ], resonant-column [ 74 , 75 , 76 , 77 ], centrifuge [ 78 , 79 ], hollow cylinder [ 80 , 81 , 82 ], calibration chambers [ 83 , 84 ], true triaxial and cubical cel apparatus [ 85 , 86 ]. Some examples are presented in Section 6 .…”
Section: Modern Measuring Systemsmentioning
confidence: 99%
“…Another interesting solution was proposed by Lee et al [ 71 ] from Korea universities, who evaluated the effect of side friction (in conditions of full or incomplete sample saturation) on the stress dependence of the elastic wave velocities on the top and bottom of the silica sand sample in an odometer. For this purpose, they were modified an odometer cell by installing a pair of piezo disk elements and a pair of bender elements at both top and bottom plates ( Figure 17 ).…”
Section: Interesting Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bender element test is considered to be one of the outstanding non-destructive tests for numerous reasons, such as its capacity for real-time monitoring [ 1 ]. In combination with piezoelectric sensors, the bender element can effectively determine the shear wave velocity and the initial shear modulus of materials in studies [ 2 , 3 , 4 , 5 , 6 ]. As an example, the bender element test was applied to studying soil characteristics, e.g., thawing and stress restoration in artificial frozen sandy soils [ 7 ], transition evaluation of fine sand from capillarity to cementation [ 8 ], expansion-induced crack propagation monitoring in rocks [ 9 ], response monitoring of transitional mixtures retaining the memory of in-situ overburden pressure [ 10 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Youn et al [ 9 ] incorporated BEs into resonant column and torsional shear testing equipment, and they compared the values of the shear wave velocities obtained from the resonant column test, torsional shear test, and BEs. Lee et al [ 31 , 32 ] suggested a new oedometer cell with BEs to evaluate both the compressibility of soils and the shear wave velocities under the zero-lateral strain condition. Byun et al [ 33 , 34 ] showed that the BE could be used to monitor the stiffness characteristic of soils during direct shear tests.…”
Section: Introductionmentioning
confidence: 99%